Immunotherapy for triple-negative breast cancer: A molecular insight into the microenvironment, treatment, and resistance - Xupeng Bai (Elsevier, 2021)
Clinicians have very limited options to treat triple-negative breast cancer (TNBC) due to the lack of effective targeted drugs. Recently, the findings of the mechanism underlying tumor-intrinsic immune escape have fueled a wave of studies into immunotherapy in breast cancer (BC). Compared with other BC subtypes, TNBC shows a better response to immunotherapy due to the higher level of tumor mutation burden and lymphocyte infiltration. Thereinto, immune checkpoint inhibitors (ICIs) achieved the first success of immunotherapy for TNBC and are widely utilized with conventional treatments in the neoadjuvant/adjuvant and advanced stages. However, a large number of TNBC patients fail to demonstrate a good response to ICIs, and the acquired resistance to ICI-based therapies is clinically emerging, which is a major challenge for immunotherapy in TNBC. Here we review the latest advances in TNBC immune microenvironment, immunotherapy, and immunotherapeutic resistance and discuss the challenges and potential approaches to improve the clinical benefit of immunotherapy against TNBC.